People's Republic of China : Financial System Stability Assessment-Press Release and Statement by the Executive Director for People's Republic of China. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses the findings of the Financial System Stability Assessment (FSAP) for China. Since the 2011 FSAP, China's impressive economic growth has continued, and it is now undertaking a necessary but prolonged economic and financial transformation. However, tensions have also emerged in various areas of the Chinese financial system. The monetary and fiscal policies aimed at supporting employment and growth have been expansionary in recent years. Pressures to keep nonviable firms open are strong, particularly at the local government level, where these objectives, at times, conflict with financial stability. The demand for high-yield investment products coupled with strengthening oversight of the banking sector has also led to regulatory arbitrage and the growth of increasingly complex investment vehicles.